Characterization of the Grasshopper Parametric Design system as a means of capturing and representing design knowledge - Parolin, Guilherme; Gadis Ribeiro, Vinicius; Miotto Bruscato, Léia (InfoDesign, 2024)
Knowledge generated in design projects, properly captured and represented through Design Rationale systems, can be seen as a source of unique value and, therefore, as a source of competitive advantage for organizations. In this context, the potential of the Grasshopper Parametric Design system as a Design Rationale system is explored by comparing it to conventional gIBIS and QOC systems. Three comparative analysis criteria are applied: 1) syntax; 2) representativeness of design parameters and their relationships; and 3) representativeness of informational flow, in which, based on the DIKW framework, the informational processes performed in the use of the analyzed systems - research, ideate, evaluate, relate, and apply - are related to the four informational levels - data, information, knowledge, and wisdom. Analysis points to evidence that Grasshopper can be considered a Design Rationale system and suggests potential differentials compared to conventional systems, as well as directions for future research.